Pengaruh Motivasi, Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan SGP Region IX Kalimantan PT Bank Mandiri (Persero) Tbk - Nur Fajrina; Irwansyah (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
This study aims to determine and test the variables of motivation, leadership and work environment on the Performance of SGP Region IX Kalimantan Employees at PT Bank Mandiri (Persero) Tbk. This study aims to identify and analyze the factors that influence the interest of accounting students in choosing a career as a public accountant. Sampling in this study using Saturated Sampling technique. Based on these criteria, the total number of employees from all employees of SGP Region IX Kalimantan PT Bank Mandiri Persero (Tbk), a total of 505 employees. The data analysis technique in this study used multiple linear regression analysis which was processed with the SPSS 25 application. Based on the results of the research conducted, it can be concluded that the motivation variable (X1) has a sig value of 0.352 which is declared insignificant, the leadership variable (X2) has a sig value of 0.879 which is declared insignificant. While the work environment variable (X3) has a sig value of 0.089 which is not significant